2015
DOI: 10.1002/cyto.a.22647
|View full text |Cite
|
Sign up to set email alerts
|

Microparticle analysis in disorders of hemostasis and thrombosis

Abstract: Microparticles (MPs) are submicron vesicles released from the plasma membrane of eukaryotic cells in response to activation or apoptosis. MPs are known to be involved in numerous biologic processes, including inflammation, the immune response, cancer metastasis, and angiogenesis. Their earliest recognized and most widely accepted role, however, is the ability to promote and support the process of blood coagulation. Consequently, there is ongoing interest in studying MPs in disorders of hemostasis and thrombosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 179 publications
(159 reference statements)
1
85
0
4
Order By: Relevance
“…It is interesting to note that the density of active TF on microvesicles is higher than that on their parental cells [30], which supports the hypothesis that MP formation is not an entirely random process and that MPs are effective products made in response to a changing environment. More recent data showed that MPs not only propagate coagulation by exposing PS but also initiate thrombin generation independently of TF and the extrinsic pathway [24]. These findings shed new light on the procoagulant properties of MPs and their possible hypercoagulable impact.…”
Section: Prothrombotic Role Of Mpsmentioning
confidence: 74%
See 4 more Smart Citations
“…It is interesting to note that the density of active TF on microvesicles is higher than that on their parental cells [30], which supports the hypothesis that MP formation is not an entirely random process and that MPs are effective products made in response to a changing environment. More recent data showed that MPs not only propagate coagulation by exposing PS but also initiate thrombin generation independently of TF and the extrinsic pathway [24]. These findings shed new light on the procoagulant properties of MPs and their possible hypercoagulable impact.…”
Section: Prothrombotic Role Of Mpsmentioning
confidence: 74%
“…Different methods and combinations of methods have been developed to detect and analyze MPs [16,20,24,25,31,32]. Appropriate sampling conditions, processing, and sample storage are essential [33].…”
Section: Mps Detection and Limitations Of The Current Available Methodsmentioning
confidence: 99%
See 3 more Smart Citations